AUDIT MANAJEMEN ATAS SISTEM BAGI HASIL PADA BANK SULSELBAR SYARIAH CABANG MAKASSAR - faniansah, nur; Sriwahyuni, Sriwahyuni (Jurnal Ar-Ribh, 2019)
This study aims to determine the Management Audit of the profit sharing system implemented by PT. Bank Sulselbar Syariah Makassar Branch. The research method used by the author is descriptive analysis and comparative analysis to explain the phenomenon of phenomena that occur at the Bank. This method is carried out to determine the suitability of the system and the reality of management audits of the revenue sharing system, especially mudharabah financing applied by PT. Bank Sulselbar Syariah Makassar Branch. Data in the form of journals and data obtained in the form of writing in the form of a general description of the company, obtained through research that is collecting data with documentation and interviews relating to the problems examined at PT. Bank Sulselbar Syariah Makassar Branch. The results of the study show that the reality of management audits of the profit sharing system, especially mudharabah financing, is in accordance with the procedures implemented by PT. Bank Sulselbar Syariah Makassar Branch.